Split-Block Graft Versus Cortico-cancellous Block Graft for Horizontal Ridge Augmentation: Cone Beam Computed Tomography and Histomorphometric Study - Botros, Mina; Kamal Adbel Gaber, Hala; Abbas, Effat; El-Mofty, Mohamed; Bissar, Mohamed (Brazilian Dental Science, 2021)
Objective: The aim of this study was to compare the horizontal dimensional changes of split-bone block and cortico-cancellous block graft in horizontal ridge augmentation using Cone Beam Computed Tomography (CBCT). The quality of the regenerated bone in both groups was compared histologically and histomorphometrically. Material and methods: Twenty patients were randomly divided in two equal groups (n= 10): Split-bone block group which was harvested from the external oblique ridge or cortico-cancellous block graft group which was harvested from the mandibular symphysis. Pre-augmentation crestal ridge width was measured using bone caliper. CBCT scans were taken on the 2nd week and 4th month post-operatively to measure crestal and total horizontal ridge dimensions. A biopsy was collected from the regenerated ridge immediately before implant insertion on the 4th month post-operatively. Results: Pre-augmentation crestal bone widths of both groups were comparable (P= 0.870). On the 2nd week and 4th month post-operatively, split-bone block showed a significantly wider crestal (P= 0.028 and P= 0.001 respectively) and total horizontal ridge dimension (P= 0.025 and P= 0.002 respectively), and on the 4th month post-operatively, it showed significantly lesser resorption at crest (P= 0.040) and in total horizontal ridge dimension (P= 0.017) than cortico-cancellous block. Histologically, the regenerated bone quality was similar in both groups. Histomorphometric analysis showed a non-significant difference in percentage of mature (P= 0.365) and immature collagen (P= 0.531) between both groups. Conclusion: Split-bone block maintained a significantly wider ridge and experienced less resorption after 4 months than the cortico-cancellous block graft, with no difference in regenerated bone quality between both groups. Keywords Dental implants; CBCT; Cortico-cancellous block graft; Histomorphometric analysis; Split-bone block technique.